2021
DOI: 10.1038/s41598-021-99248-2
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination intentions generate racial disparities in the societal persistence of COVID-19

Abstract: We combined survey, mobility, and infections data in greater Boston, MA to simulate the effects of racial disparities in the inclination to become vaccinated on continued infection rates and the attainment of herd immunity. The simulation projected marked inequities, with communities of color experiencing infection rates 3 times higher than predominantly White communities and reaching herd immunity 45 days later on average. Persuasion of individuals uncertain about vaccination was crucial to preventing the wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Some scientists endorsed the official rhetoric ( 19 – 23 ). Supporters concluded that the more virulent Delta variant posed a risk to the “pandemic of the unvaccinated” before the eventual attainment of herd immunity ( 24 ), particularly in-person schools ( 25 ), and Black, Indigenous, and People of Color (BIPOC) ( 26 ). Dr. Hooper strongly urged that healthcare workers (HCWs) should get their jabs in her editorial ( 27 ), as well as Kelly and Jackson ( 28 ).…”
Section: Resultsmentioning
confidence: 99%
“…Some scientists endorsed the official rhetoric ( 19 – 23 ). Supporters concluded that the more virulent Delta variant posed a risk to the “pandemic of the unvaccinated” before the eventual attainment of herd immunity ( 24 ), particularly in-person schools ( 25 ), and Black, Indigenous, and People of Color (BIPOC) ( 26 ). Dr. Hooper strongly urged that healthcare workers (HCWs) should get their jabs in her editorial ( 27 ), as well as Kelly and Jackson ( 28 ).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, this method could apply to datasets in other countries or regions during different pandemics to investigate the local virus diffusion pattern. The method could also be used to investigate the neighborhood-level virus spreading and, following our prior research [67], provide a new perspective to understand the racial disparities among communities. and many other nations began to distribute vaccines to high-risk groups shortly thereafter and then extended distribution to the general public in the spring.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has become a widely used source to understand various aspects of human mobility behaviors, and their applications extend to customer behavior analysis [12,13], urban planning [14,15], disaster recovery [16,17,18], public health [19,20,21,5,22] and beyond.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation